Par de Lax, simetrias de calibre, transformações de Backlünd e Sólitons de massa e velocidade variáveis do tipo Seno-Gordon - Costa, José Parreira Borges (2016)
In this work, we will study some properties of the Lax pair without spectral para- meter and its applications in the study of some two-dimensional integrable models, such as the climb free-field models, models of sine-Gordon (SG), senh-Gordon (ShG), Liouville (LL) and sine-Liouville (SGL). Besides, we consider the sine-Gordon mo- del of variable mass (VMSG). We studied the Backlünd transformations (TB) th- rough the symmetries of the equations of Ricatti and apply them in obtaining type soliton solutions and in the construction of conserved charges to the SG model. For the model LL we use a TB to obtain the general solution of the model. Also, we use the deformed TB in order to obtain the 1-soliton solution of the VMSG model.